The Effect Of Early Detection Of Growth and Development Training For Posyandu Caders On Knowledge and Skill Of Motor Stimulation In Darungan Village - Susanti Tria Jaya; Eva Nur Azizah; Vide Bahtera Dinastiti (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The independent variable is early detection training for posyandu craders, with an interval scale. Dependent Variable, namely Knowledge and Skills About Motor Stimulation. The instruments used were questionnaires and observation sheets, with an interval scale. Statistical analysis using the T- Test on the effect of early detection training on the development of posyandu cadres to knowledge of motor stimulation with a value of p = 0.000 means at 5% alpha. This showed that there was an effect of early detection of growth and development training for posyandu caders on knowledge of motor stimulation. The results of statistical tests showed that the value of p = 0.000 means that at 5% alpha. This showed that there was an effect of early detection of growth and development training for posyandu caders on skill of motor stimulation. So that it an increased of 21.33 % and 19,04 %.